Status of Nepalese Orphan through Parental Death in Foreign Labour Migration - Adhikari, Govinda Prasad; Paudel, Thuma Kumari (Cognition, 2022)
Migration is one of the components of the demographic Process. Parental migration has both positive and negative impacts on child development. Trends of death and injury in foreign labour migration are increasing. The death rate of male migrants is higher than female migrants in foreign employment. Parental deaths were observed higher for province one. The absence of the parents will impact the health and education of children. This study aims to analyse the impact on Nepalese orphans through parental death in foreign labour migration. This study has used quantitative information through secondary sources to achieve the research objectives. The major secondary sources are national and international publications, reports and journals. Information on school students, the injured or death status of the parents and scholarship status of children has been collected from the foreign employment promotion board of Nepal. All provinces are purposively selected as most foreign labour migrant provinces. Finally, data were presented in tabular and graphic form. Data were analysed in a descriptive method. The death of foreign labour migrants is increasing in Nepal. The absence of parents due to foreign labour migration in the family has increased negative effects on child health and education. The major causes of parental death are disease, accident, natural cause and investigation pending. The major death occurrence countries are Saudi Arabia, Malaysia and Qatar. The government’s major social programs to support orphan and their families are injury benefit compensation and student scholarship programs, medicine support, rescue, and transportation of the dead body, orientation and training and other support